Acute Ischemic Stroke Secondary to Iron Deficiency Anemia: A Case Report. (9th May 2012) - Mehta, Preema J.; Chapman, Sherita; Jayam-Trouth, Annapurni; Kurukumbi, Mohankumar
Abstract : A rare case of acute ischemic stroke in a young patient with iron deficiency anemia (IDA) is reported. IDA has been suggested to have an association with stroke, but few cases have proven it thus far. Three physiological mechanisms explaining IDA to ischemic stroke include a hypercoagulable state secondary to IDA, thrombocytosis secondary to IDA, and anemic hypoxia induced by IDA. Our paper shows an example of a hypoxia-induced stroke secondary to IDA in a young woman with menorrhagia. Thrombus formation was ruled out as the Magnetic Resonance Angiogram (MRA) showed no evidence. As all other known causes for stroke were ruled out, the patient's IDA is a reasonable cause for her stroke. Iron deficiency decreases the amount of hemoglobin, which consequently decreases the amount of oxygen in the blood resulting in low-oxygen delivery to the brain. This causes hypoxic conditions in the brain, leading to death of brain tissue. Thus, we suggest a possible relationship between IDA and ischemic stroke in young adults. Considering IDA as one of the risk factors for ischemic stroke and treating with timely transfusions would be an important step one can take to prevent stroke.